Experience and Expression: Social and Cultural Significance in the Fear of Crime - Jackson, Jonathan (The British journal of criminology, 2004)
This paper argues that to ignore the social meaning that constitutes public perceptions of crime is to offer a shallow picture of the fear of crime - and survey research need not do either. Examining the symbolic links between community cohesion, disorder and crime, this study suggests that perceptions of risk are explicably situated in individuals' understandings of the social and physical make-up of their neighbourhood, as well as vulnerability and broader social attitudes and values. Furthermore, an explanation is offered for recent research that suggests that the prevalence of fear of crime has been exaggerated. Namely, survey responses may articulate both experienced' fear - summations of the frequency of emotion - and expressive' fear, or attitudes regarding the cultural meaning of crime, social change and relations, and conditions conducive to crime